Surgical treatment of secondary hip osteoarthritis using cementless total hip endoprosthesis with Fitmore® Hip Stem – a case report - Golubović, Ivan; Baščarević, Zoran; Stojiljković, Predrag; Radovanović, Zoran; Golubović, Ivana; Radojković, Milan; Djordjević, Dušan; Mitić, Aleksandar; Milijić, Svetlana; Golubović, Zoran (Vojnosanitetski pregled, 2017)
Introduction. Hip dysplasia with subluxation represents insufficient coverage of the femur’s head placed in the dysplastic acetabulum. This lack of coverage ranges from barely noticeable to condition where half of femur head is uncovered by acetabulum. The caput-collum-diaphyseal angle of the proximal femur and anteversion angle of collum are increased, Wiberg’s angle is less than 15° and Ménard-Shenton line is interrupted. Hip joint degeneration occurs very early. When radiological signs of hip joint degenerative changes are discovered in elderly they are associated with pain, limited movements and leg shortening. Case report. We present a 53-year old female treated conservatively in childhood because of hip diyplasia with subluxation. After pregnancy, right hip pain emerged. Clinical and radiological examinations revealed hip subluxation with the signs of degenerative osteoarthritis. Initial treatment was conservative and included drugs and balneophysical procedures. Since pain and movement impairment progressed and became constant, a hip replacement using cementless total endoprosthesis with Fitmore® Hip Stem was done. In the pre-operative preparation, anteroposterior x-ray of the hip(with third of the proximal femur) was made. This X-ray enabled precise planning of implantation endoprosthesis component. The early postoperative course was uneventful with very good therapeutic effect. Following successful physical rehabilitation, the patient returned to work and full life activity. Conclusion. Implantation of the cementless endoprosthesis with Fitmore® Hip Stem in the treatment of secondary hip osteoarthritis is a good choice in the treatment of young patients with good bone quality. Future clinical and radiological follow-up and comparative studies are needed to show the advantages of this type of stem compared to the classical cementless long stem.